Curcuma mangga Ethanol Extract Improves Sperm Quality of Mice Exposed to Monosodium Glutamate - Silvia Aini; Marhendra , Agung Pramana Warih; Rahayu, Sri (The Journal of Experimental Life Science, 2022)
The current study aimed to determine variations effect in the dose of Curcuma mangga ethanol extract on male mice exposed to monosodium glutamate (MSG). The 24 adult male mice with the body weight of 25-30 g and 3-4 months old were used, then divided into six groups (n= four per group). The groups are K- (untreated mice), K+ (induced MSG) for 45 days, P1 (MSG + C. mangga extract 25 mg.g-1 BW), P2 (MSG + C. mangga extract 50 mg.g-1 BW); P3 (MSG + C. mangga extract 75 mg.g-1 BW); and P5 (MSG + C. mangga extract 100 mg.g-1 BW) for 30 days. Animals were dissected on the 46th day. The epididymis was isolated, and sperm quality was evaluated. The results showed that25-75 mg.g-1 BW C. mangga ethanolic extract could increase sperm viability by 24-29%, while at a dose of 25-100 mg.g-1 BW the sperm motility decreased by 58-92%. The administration of 100 mg.g-1 BW C. mangga could decrease it by 58% and concentration at a dose of 100 mg.g-1 BW increased sperm concentration by 96%. The use of MSG can increase sperm abnormalities compared to controls. This study showed that C. mangga effectively improved the sperm quality of mice exposed to MSG. Keywords: Curcuma manga, Epididymis, Monosodium Glutamate, Sperm quality.